Along-strike variation in slab geometry at the southern Mariana subduction zone revealed by seismicity through ocean bottom seismic experiments. Issue 3 (10th June 2019) - Zhu, Gaohua; Yang, Hongfeng; Lin, Jian; Zhou, Zhiyuan; Xu, Min; Sun, Jinlong; Wan, Kuiyuan
SUMMARY: We have conducted the first passive Ocean Bottom Seismograph (OBS) experiment near the Challenger Deep at the southernmost Mariana subduction zone by deploying and recovering an array of 6 broad-band OBSs during December 2016–June 2017. The obtained passive-source seismic records provide the first-ever near-field seismic observations in the southernmost Mariana subduction zone. We first correct clock errors of the OBS recordings based on both teleseismic waveforms and ambient noise cross-correlation. We then perform matched filter earthquake detection using 53 template events in the catalogue of the US Geological Survey and find >7000 local earthquakes during the 6-month OBS deployment period. Results of the two independent approaches show that the maximum clock drifting was ∼2 s on one instrument (OBS PA01), while the rest of OBS waveforms had negligible time drifting. After timing correction, we locate the detected earthquakes using a newly refined local velocity model that was derived from a companion active source experiment in the same region. In total, 2004 earthquakes are located with relatively high resolution. Furthermore, we calibrate the magnitudes of the detected earthquakes by measuring the relative amplitudes to their nearest relocated templates on all OBSs and acquire a high-resolution local earthquake catalogue. The magnitudes of earthquakes in our new catalogue range from 1.1 to 5.6. The earthquakes span over the Southwest Mariana rift, the megathrust interface, forearc and outer-rise regions. While most earthquakes are shallow, depths of the slab earthquakes increase from ∼100 to ∼240 km from west to east towards Guam. We also delineate the subducting interface from seismicity distribution and find an increasing trend in dip angles from west to east. The observed along-strike variation in slab dip angles and its downdip extents provide new constraints on geodynamic processes of the southernmost Mariana subduction zone.